Potential active compounds of Streptomyces sennicomposti GMY01 for antiplasmodial and antiSARS-CoV-2 revealed by targeted metabolomic and molecular docking - Damayanti, Ema; Nisa, Khoirun; Febriansah , Rifki; Hadi, Ismanurrahman; Dinoto, Achmad; Widada, Jaka; Mustofa (Faculty of Medicine, Public Health, and Nursing Universitas Gadjah Mada and Indonesian Pharmacologist Association or Ikatan Farmakologi Indonesia (IKAFARI), 2024)
Streptomyces sennicomposti GMY01 is a bacterium with huge biotechnological potential that revealed by genome mining analysis. This research aimed to investigate the potential compounds as antiplasmodial and the antiSARS-CoV-2 from the S. sennicomposti GMY01 using targeted metabolomic and in silico molecular docking. The crude extract was obtained by extraction of supernatant from fermentation product of the S. sennicomposti GMY01. The secondary metabolite profiling was obtained by using ultra-high-performance liquid chromatography (UHPLC) coupled to targeted high-performance mass spectrometry (HRMS) based on genome mining data of whole genome sequence (WGS). In silico molecular docking was performed on important target protein of P. falciparum i.e. glutathione reductase (PfGR), lactate dehydrogenase (PfLDH), phosphoethanolamine methyltransferase (Pfpmt), erythrocyte membrane protein 1 (PfEMP1) and glutathione-S-transferase (PfGST); and of SARS-CoV-2 proteins i.e. protease domain, spike glycoprotein, receptor-binding domain angiotensin-converting enzyme 2 (RBD-ACE2), 3-chymotrypsin-like protease (3CLpro), and RNA-dependent RNA polymerase (RdRp). One compound from S. sennicomposti GMY01 extract, albaflavenone was confirmed by targeted LC-HRMS. On molecular docking analysis, albaflavenone showed higher affinity than chloroquine as antiplasmodial drug and exhibited same affinity to remdesivir as antiSARS-CoV-2. Stertomyces sennicomposti GMY01 has promising biotechnological potential for drug development as antiplasmodial and anti-SARS-CoV-2 agent. Further study is needed, especially regarding in vitro testing of albaflavenone as antiplasmodial and antiSARS-CoV2.